Scaling Education to Marginalized Populations: Long-Run Impacts of Technology-Aided Schools - Raissa Fabregas; Laia Navarro-Sola (CESifo GmbH, 2025)
Millions of children worldwide remain out of school due to the high costs of reaching them and a shortage of qualified teachers. Can ICT-based instruction help close this gap and deliver the long-term benefits of traditional schooling? This paper provides causal evidence on the long-term educational and labor market effects of using ICT to expand last-mile access to post-primary education. We focus on Mexico's TV-schools –physical lower secondary schools that replace most on-site teachers with televised instruction– one of the largest formal mass media-based education models globally, serving over 1.4 million children every year. Exploiting nationwide geographic variation and cohort exposure to TV-school openings during 1980-2000, we find that high exposure to TV-schools increased lower secondary graduation by 8 percentage points, educational attainment by 0.4 years, and it led to a long-term 8% increase in hourly earnings. We show evidence that most TV-school students would have otherwise remained out of school, and that the labor market returns from additional schooling are comparable to those from standard secondary schools. The program benefits both agrarian and more economically diversified areas, with those in the latter experiencing three times higher earning gains. Our findings show that low-tech, scalable educational models can be a cost-effective way to generate significant labor market returns in underserved regions, even before high-tech solutions become widespread.
Keywords: I20; J24; O15; 330